Aid for trade 2011 : results emerging from the case stories (OECD/WTO ParisFR, 2011)
Reviews case stories on aid for trade in order to probe more deeply into objectives, challenges and processes so as to better understand results of trade-related assistance - particularly, what worked, what were the key ingredients of success, and what could governments and practitioners learn from the experience.
Keywords: TRADE